Islamic bioethics viewpoint on elective brain chip implants and brain computer interfaces for enhancing academic performance in competitive examinations - Chin, Alexis Heng Boon; Roslan, Rosazra; Alsomali, Nimah; Al‑Balas, Qosay; Salhab, Belal Barakat Sulaiman; Muhsin, Sayyed Mohamed (Springer Nature, 2026)
The first implantation of a brain chip into a human paralysis patient by Neuralink demonstrated much potential for treating debilitating neurological diseases and injuries. Nevertheless, brain chips can also be implanted in healthy people to provide an interface between the human brain with computers, robotic machines, and novel artificial intelligence platforms, which generates new ethical issues. The focus here is on the development of brain chip implants that can significantly improve memory, intelligence, and cognition, thereby boosting performance in national examinations for university admissions and securing civil service jobs, thus providing a “game-changer” and “shortcut” for many students and parents. Given that Islam is a major world religion, constituting a significant portion of the global population, it is crucial for the biomedical industry to comprehend Islamic perspectives on emerging medical technologies, which will enable it to more effectively cater to a substantial and growing demographic. We thus critically examine whether the application of brain chip technology to enhance academic performance in highly competitive examinations is consistent with Islamic principles. Based on the Islamic jurisprudential framework, such an application for intellectual enhancement of normal and healthy people without any mental impairment may conflict with the injunction to preserve intellect (Hifz al-Aql) and “consideration of consequences” (murāʿāt al-ma'ālāt) in Islam. It may also be viewed as tampering with Allah’s creation (Taghyir Khalq Allah). Gaining such unfair advantages in competitive examinations will likely be viewed as unethical, by transgressing the core Islamic precepts of Amanah (trustworthiness), Al-‘Adl (justice), Ikhlas (sincerity), and Mujahadah (striving).